Inventory of Termites and Biogenic Structures in the Forest Adjoining the "Palm Trees" Restaurant of Felix Houphouet-Boigny University Campus (Abidjan - South Cote D’ivoire) - Moise, Akpesse Akpa Alexandre; Victoire, Bassa Amenan N’Nezou; Dohouonan, Diabate; Tenon, Coulibaly; Perrine, Kissi Therese Appoh; Herve, Koua Kouakou; Philippe, Kouassi Kouassi (International Research Journal of Insect Sciences, 2022)
Termites play an important ecological role. Thus, this study was carried out in the forest adjoining restaurant "the palm trees of the university campus of Cocody" to determine the species of termites and their impacts on the trees of this forest. Three transects of 100m long and 2m wide each subdivided into 20 sections and Tropical soil biology and fertility (TSBF) monoliths were developed. Then a systematic excavation was carried out along transects in search of termites. Then the plot containing transects was prospected in order to identify termite mounds and biogenic structures. After inventory, we identified 7 species of termites: Macrotermes bellicosus, Microtermes sp, Basidentitermes sp, Odontotermes sp, Pericapritermes sp, Amitermes guineensis and Ancistrotermes guineensis. Wood-feeders, fungus-growers and soil-feeders are the trophic groups found on the site. Fungus-growers were the group with the most species. We recorded a 25% attack rate on the trees from transects. A total of 13 nests were counted including 9 epigeal termite mounds and 4 arboreal nests. The low richness recorded shows that our plot is heavily anthropized. The conservation or maintenance of this site would allow species to recolonize this space.